2019
DOI: 10.1186/s13023-019-1192-4
|View full text |Cite
|
Sign up to set email alerts
|

New insights on congenital pulmonary airways malformations revealed by proteomic analyses

Abstract: BackgroundCongenital Pulmonary Airway Malformation (CPAM) has an estimated prevalence between 0.87 and 1.02/10,000 live births and little is know about their pathogenesis. To improve our knowledge on these rare malformations, we analyzed the cellular origin of the two most frequent CPAM, CPAM types 1 and 2, and compared these malformations with adjacent healthy lung and human fetal lungs.MethodsWe prospectively enrolled 21 infants undergoing surgical resection for CPAM. Human fetal lung samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
3
7
0
3
Order By: Relevance
“…This finding is an accordance with a previous report showing cystic malformation caused by deficiency of the Wnt receptor Frizzled 2 in branching airway epithelium [19]. With regard to transcription factors, diffuse expression of SOX9 and SOX2 in the epithelial cells lining the cystic lesion of CPAM type 1 and 2 have been reported [3,26]. This suggests disrupted regulation of the respective genes in the cystic lesions.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is an accordance with a previous report showing cystic malformation caused by deficiency of the Wnt receptor Frizzled 2 in branching airway epithelium [19]. With regard to transcription factors, diffuse expression of SOX9 and SOX2 in the epithelial cells lining the cystic lesion of CPAM type 1 and 2 have been reported [3,26]. This suggests disrupted regulation of the respective genes in the cystic lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, 860 up-regulated genes and 203 down-regulated genes were obtained. The sequence information of this whole transcript suggested that Nkx2-1 was normally expressed, Hoxb-5 was normally expressed and Sox2 was highly expressed, and the results were the same as those of other scholars 35 . BMPs belong to the TGF-β family, and several BMPs and their receptor BMPR play regulatory roles in lung development 1 , 35 .…”
Section: Discussionsupporting
confidence: 79%
“…El Tipo I es el más frecuente de las MCVAP y tiene el mejor pronóstico, debido a que son localizadas y solo afectan a una parte de un lóbulo, también puede ser multiloculados (4) . La mayoría está presente en el periodo neonatal o en el intrauterino, pero en casos infrecuentes puede presentarse más tarde.…”
Section: Tipo 4 Numerosos Quistes De Origen Acinarunclassified